Seletividade de herbicidas aplicados sobre plantas de cobertura de inverno e verão - Dal Bosco, Ezequiel (2018)
Cover plants are of great importance for agriculture today, aiming at production, but also the conservation and preservation of the soil, with the aim of improving its quality. One of the limitations of its use is the lack of registered herbicides that are efficient for controlling weeds in cover crops. The present work has the objective of selecting different herbicides to control weeds in the cultivation of cover crops. The work was carried out in a greenhouse at the Universidade Tecnológica Federal do Paraná (UTFPR), Dois Vizinhos campus. Pots of 500 ml capacity, filled with local soil, classified as Red Latosol were used. The 17 summer and winter cover species were sown on 11/2/2017. After 20 days of sowing the herbicides were applied: 2,4-D, Metsulfuron-methyl, Chlorimuromethyl, Fomesafen, Nicosulfuron, Fluazifop- p-butyl and Bentazone. After application of herbicides, phytotoxicity evaluations were performed at seven, 14, 21, 28 and 35 days. For these evaluations a visual scale of phytotoxicity was used, from zero to 100% where zero the plants were intact and 100% were dead plants. The results were tabulated and the statistics were used to obtain the means, using Win Sat with Tukey's test at 5%, and for the interaction between the plants and the herbicides was used Scott knott. As final results obtained in the evaluation at 35 days AAP, the 2,4-D is selective for fescue, also the pueraria, presenting 0% of phytotoxicity, also for c. breviflora and c. juncea, with values of 05% and 20% of phytotoxicity. For the herbicide Metsulfuron metilico the selection of m. with 4.5% phytotoxicity, and m. gray with 05%, 13% for quinoa and 23.7% for fescue. With the herbicide chlorimuron the results of plant selection were with the gray and ragged mucosa with 0% of phytotoxicity, pueraria and lab lab with 05% and the bean with 10%. For the herbicide fomesafem the best result was pueraria with 0% of phytotoxicity, followed by fescue, red clover and lab lab with 20%, 32,5% and 40% of phytotoxicity. Nicosulforon caused the death of practically all species, with the exception of mucuna with 20% of phytotoxicity and c. ocroleuca with 22.5% results that can still recover. The herbicide Fluazifope-p-butyl had the best results when applied on the dicotyledons. The herbicide bentazone caused the death of five species being the Lupine, Cosmos, Quinoa, Crambe and Forage Chicory, for the rest of the species it had a selective character. It is concluded that to have greater confirmation of the results will be necessary to carry out field tests.